Using Ocs Module To Improve Working Adults’ Confidence Level In Speaking - Adnan, Nur Ilianis (2019)

(untitled)
There are many ways to improve Malaysian working adults’ confidence level in speaking English and one of the ways is through modules. Through a widespread literature review, it is shown that oral tasks in modules managed to improve one’s confidence level in speaking English. Therefore, in this study, it is expected to improve working adults’ confidence level through oral communication skill (OCS) module. This is because the module offers them the opportunity to reduce anxiety level and improve the fluency of their speeches, willingness to communicate and non-verbal cues. This study with a case study design was conducted to study the effectiveness of Public Speaking Programme in improving Malaysian working adults’ confidence level in speaking English. Three working adults were chosen in this study to use the OCS Module throughout the period of 12 weeks. The working adults’ performances were recorded and were observed by the researcher. Their performances were evaluated by the evaluator and the role-players (timer who recorded the time of the working adults’ presentations and ah-counter who counted the number of fillers made by the working adults). They were also interviewed by the researcher. The interviews were done for four times throughout 12 weeks in order to check on their level of confidence from time to time. They were also asked to write reflective and narrative journals throughout the 12 weeks. At the end of the research, they were required to fill in the post-experience feedback form, which will be used to improve the module for future use.